The Relationship between Early Marriage and Mental Health in Adolescent Girls in the KUA Ngemplak Yogyakarta - Ningrum, Rhadika; Ari Astuti, Dhesi; Anjarwati (Universitas Airlangga, 2023)
Background: Early marriage occurs at the age of less than 19 years. The incidence of early marriage is caused by cultural factors of early marriage, married by accident, education, and low economic conditions all affect early marriage. The mental health impact of early marriage can lead to anxiety, stress, and depression. Aims: The purpose of this study was to determine the relationship between early marriage and mental health in adolescent girls. Methods: This study uses quantitative research methods using a cross-sectional research design. The total population is 49 people, and the sampling method used is total sampling. The study was conducted for 1 month. The research instrument used the DASS21 questionnaire and data collection sheets. The data analysis of this research was univariate and bivariate analysis. Results: The results showed that the frequency of adolescents experiencing severe stress was 40.8%, very severe anxiety reached 42.9%, and very severe depression reached 53.1%. There is a relationship between early marriage and severe stress with a p-value of 0.001, there is a relationship between early marriage and very severe anxiety with a p-value of 0.001, and there is a relationship between early marriage and very severe depression with a p-value of 0.004. Conclusion: It can be concluded that early marriage has a relationship with mental health in adolescent girls in the Ngemplak Region and future research should involve husbands in in-depth qualitative research exploring in depth the causes of the mental health of young women who took early marriages.